Prevalence and Pattern of Oral and Maxillofacial Pathology in Al-Qassim Region, Saudi Arabia - Faraj Alotaiby; Rahaf Alruhaimi; Norah Alzamil; Ezdyan Alsemanni; Areej Almutairi; Hala Elsaka (Wiley, 2024)
Conclusion: The findings provide important information about the oral and maxillofacial pathology in Al-Qassim region, Saudi Arabia. This study found that biopsied oral lesions were more prevalent in males and in patients in the fourth decade of life. The oral mucosa was the most biopsied site, and the majority of the biopsies were soft tissue pathological lesions and radicular cyst was the most frequent diagnosis. Knowledge of such demographic and clinical features of oral and maxillofacial pathology cases helps in prediction of disease incidence and subsequent proper patient care in the region.